The Effect of Accounting Conservatism, Company Size, and Profitability on Tax Avoidance - Elon Manurung; Noviherni; kartika, Dhefitriana Azzahra (JOURNAL INTELEKTUAL, 2025)
Introduction/Main Objectives: To empirically test the effect of accounting conservatism, company size, and profitability on tax avoidance in property and real estate sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2020–2024. Background Problems: Tax avoidance is still prevalent and is influenced by company characteristics. Novelty: Using the post-pandemic period with a focus on the property and real estate sub-sector, which is rarely studied. Research Methods: This study uses a quantitative approach with multiple regression analysis using Eviews 13 software and purposive sampling of 17 companies from a total population of 93. Finding/Results: Accounting conservatism has a positive but insignificant effect, company size has a negative but insignificant effect, and profitability has a significant negative effect on tax avoidance. Overall, profitability is the most dominant factor affecting the level of tax avoidance. Conclusion: The higher the company's profitability, the lower the tendency to engage in tax avoidance, making profitability an important indicator in assessing tax compliance and providing implications for management, investors, and tax authorities in improving fiscal transparency